To find the recursive formula for the arithmetic sequence given, we need to identify the first term and the common difference.
The sequence is:
- First term (a₁): -6
- Second term (a₂): 1
- Third term (a₃): 8
- Fourth term (a₄): 15
To find the common difference (d), we subtract the first term from the second term: \( d = 1 - (-6) = 1 + 6 = 7 \)
So, the common difference \( d \) is 7.
Now we can write the recursive formula:
- The first term is: \( a_1 = -6 \)
- The recursive relation is: \( a_n = a_{n-1} + 7 \) for \( n > 1 \)
Putting this together, the correct recursive formula is:
- \( a_1 = -6 \)
- \( a_n = a_{n-1} + 7 \) for \( n > 1 \)
None of the given responses directly match this. If the options had \( a_1 = -6 \) instead of \( a_1 = -1 \), it would have matched the calculations. Based on the responses provided, it seems there might have been a misunderstanding in the options.
The correct recursive form based on the clear calculations is:
\( a_1 = -6 \) \( a_n = a_{n-1} + 7 \) for \( n > 1 \)